Neighbor-based Fast Rate Control Scheme for Basic Unit Layer for H.264/AVC Standard - Vizzotto, Bruno B.; Diniz, Cláudio M.; Bampi, Sergio (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2011: Proceedings of the 17th Brazilian Symposium on Multimedia and the Web, 2011)
In video encoding H.264/AVC is the state-of-the-art and provides efficient compression for video applications. However, by using the rate control scheme of reference H.264/AVC software, high variations in the visual image quality will be experienced. This paper presents a novel rate control scheme for the H.264/AVC standard in order to ensure the output video quality and maintain a stable output bit-stream. First, an overview of the rate control module is presented. Then a neighbor-fast based model to predict the mean of absolute difference of basic unit layer is proposed. Finally, a comparison between compromise and visual quality with related work described in the literature will be performed.